Performing National Identity - Edensor, Tim (Hagar: Studies in Society and Culture, 2002)
This paper explores how national identities are performed through different national dramas. The metaphor of performance allows us to draw on a series of related ideas around scripts, roles, stage-management, choreography, directing and improvisation to examine how national identity is staged in specific places, in both spectacular locations and mundane settings. Thus a national geography is shown to be constituted according to different spatial scales. The paper argues that the sustenance of identity depends upon unreflexive actions constituted collectively as much as through more overt ‘invented traditions’ and large ceremonies, and further contends that performances are always in process, and are apt to be contested by competing actors. And while globalising processes appear to threaten the security of national identity through the proliferation of performances both within and beyond the national, it retains a common-sense grounding in the everyday and in the dense accumulation of diverse performances around national themes.